Effect of granulated lead smelter slag on strength of fly ash-based geopolymer concrete. (15th May 2015) - Albitar, M.; Mohamed Ali, M.S.; Visintin, P.; Drechsler, M.
Highlights: Granulated lead smelter slag is an effective supplementary cementitious material. Particle size has significate influence on compressive strength. Mechanical properties of concrete with slag are similar to those with fly ash. The addition of lead smelter slag results in a decrease of the drying shrinkage. Abstract: Geopolymer concretes are manufactured from high-volume industrial waste materials in order to produce concrete that is low energy consuming, has a low carbon footprint, is sustainable and Portland cement-free. This paper presents an experimental study on the manufacture and behaviour of geopolymer concrete produced with a combination of granulated lead smelter slag (GLSS) and fly ash. The experimental program included 32 mix designs to investigate the influence of: fly ash replacement with slag as a binder, washed river sand replacement with slag as a filler, slag particle size to reactivity, alkaline activator-to-binder ratio, and curing period. It was found that incorporating 75% of slag as fly ash replacement and 100% of slag as fine aggregate produces concrete exhibiting compressive strength of 31 MPa. It was also found that significant improvements in the compressive strength of the hardened concrete (i.e., from 6 MPa to 65 MPa) could be obtained by super fine crushing the slag to a fineness similar to Portland cement and fly ash (<20 μm). The results showed that the mechanical properties of the fly ash/slag-based geopolymer concrete were similar to that of fly ash-based geopolymer concrete, whilst the drying shrinkage of geopolymer concrete containing high volume of GLSS was lower than that of fly ash-based geopolymer concrete.